Metro Wi-Fi Networks: What Are They and How Can They Benefit Your Community? - Williams, Bert (Public Management (00333611), 2007)
The article offers information on metro-scale Wi-Fi networks which offers great benefit to the community in terms of community-wide Wi-Fi access and high-speed Internet access. Such Wi-Fi network can connect all sorts of Wi-fi devices, including laptops, personal digital assistants, and Voice over Internet Protocol phones. It works through mesh technology which makes practical the distribution of Wi-Fi throughout a community by eliminating a significant logistical and economic hurdle.